2017
DOI: 10.1117/1.nph.5.1.011005
|View full text |Cite
|
Sign up to set email alerts
|

Differential efficiency of transcutaneous electrical nerve stimulation in dominant versus nondominant hands in fibromyalgia: placebo-controlled functional near-infrared spectroscopy study

Abstract: Using functional near-infrared spectroscopy (fNIRS), modulation of hemodynamic responses by transcutaneous electrical nerve stimulation (TENS) during delivery of nociceptive stimulation was investigated in fibromyalgia (FM) patients and healthy controls for both hands. Two experiments were conducted: (1) median nerve stimulation with TENS and (2) painful stimulation using electronic von Frey filaments with TENS/placebo TENS. Mean [Formula: see text] brain activity was compared across groups and conditions usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…Cognitive functions such as memory have been enhanced in FM patients by anodal transcranial direct current stimulation over the dorsolateral prefrontal cortex and has clinical relevance for top-down treatment approaches in FM [ 106 ]. In FM patients, modulation of hemodynamic responses by transcutaneous electrical nerve stimulation during delivery of nociceptive stimulation was also investigated and shown to be an effective factor in FM treatment, although the underlying mechanism for these findings still needs to be clarified [ 107 ]. It has been recently demonstrated that both transcutaneous electric nerve stimulation and acupuncture applications seem to be beneficial in FM patients [ 108 ].…”
Section: Therapymentioning
confidence: 99%
“…Cognitive functions such as memory have been enhanced in FM patients by anodal transcranial direct current stimulation over the dorsolateral prefrontal cortex and has clinical relevance for top-down treatment approaches in FM [ 106 ]. In FM patients, modulation of hemodynamic responses by transcutaneous electrical nerve stimulation during delivery of nociceptive stimulation was also investigated and shown to be an effective factor in FM treatment, although the underlying mechanism for these findings still needs to be clarified [ 107 ]. It has been recently demonstrated that both transcutaneous electric nerve stimulation and acupuncture applications seem to be beneficial in FM patients [ 108 ].…”
Section: Therapymentioning
confidence: 99%
“…In the clinical environment, investigators have studied thermal stimuli-triggered dental pain, 52,54,120,131 surgeryinduced pain, 42,72,73,95,122,135 acupuncture-evoked pin-prick pain, 38,129 and similar venipuncture pain on infants. 10,106,107,128,130,142 On the other hand, in the experimental environment, researchers have studied acute pain conditions triggered by thermal, 7,8,13,37,51,119,174 mechanical, 10,13,42,49,51,76,106,129,131,142,157,159,160 electrical, 2,35,96,109,110,125,175 and chemical 40,56 stimulations, even pain imagery 170,…”
Section: Functional Near-infrared Spectroscopy Experiments Protocol D...mentioning
confidence: 99%
“…1). Researchers have used breath-holding tasks, 4,5,28 pressure stimulation, 68,157 verbal fluency task, 29,126,157 finger tapping task, 43,45 transcranial magnetic stimulation 147 and transcranial electrical nerve stimulation, 34,36 and medicine injection 164 to study patients' brain activation under chronic pain conditions such as migraine, 158 fibromyalgia, chronic lower back pain, neuropathic pain, and somatoform pain disorder.…”
Section: Functional Near-infrared Spectroscopy Experiments Protocol D...mentioning
confidence: 99%
“…Differences in pain perception between right and left hands were assessed before [35], [36]. In our cohort, we heated the right hand in 23 subjects and the left hand in the remaining 12 participants.…”
Section: E E E P R O O Fmentioning
confidence: 99%